Marketing Strategy to Improve Land Sales in Sei Mangkei Special Economic Area (Case Study at PT Kawasan Industri Nusantara) - Ginting, Hans Giovani; Lumbanraja, Prihatin; Sugiharto, Sugiharto (Universitas Syiah Kuala, 2025)
Developments in the line of business must be carried out in conjunction with a good marketing strategy. As the marketing strategy that has been employed has not been optimal, PT Kawasan Industri Nusantara (KINRA) aims to increase land sales in KEK (Special Economic Zone) Sei Mangkei. This descriptive research is conducted qualitatively, where some of the qualitative data obtained is subsequently converted into quantitative data using a measurement scale of weights and ratings commonly used in SWOT analysis. The research object is determined through observation, interviews to determine the issue related to the implemented marketing strategies, along with documentation and relevant literature to support the research problems. Furthermore, SWOT analysis is used in this research to improve and enhance the marketing strategy that has been done. The research concludes that the company still implements conservative marketing strategies and has not utilized digital marketing methods, such as billboard advertising and social media advertising, among others. The strategy suitable for establishing the competitive strategy of PT Kawasan Industri Nusantara (KINRA) is the stable growth strategy. This means that in the future developments, PT Kawasan Industri Nusantara (KINRA) can implement a Role Growth strategy, but it should be executed gradually based on a priority scale. To develop its marketing strategy, PT KINRA must take an important step, namely: in the short term, the company is required to recruit more marketing employees. In addition, the company also requires to develop a website as an effective promotional tool to introduce the company's services to public.